2016
DOI: 10.3906/elk-1411-63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transverse magnetic field on low pressure argon discharge

Abstract: A numerical simulation was performed to investigate the effect of transverse magnetic fields on low pressure argon plasma. Discovering the variations in electric field, electric potential, power consumption in plasma, and dominant physical mechanisms after application of magnetic fields is the main output of this analysis. A simulation was performed using the finite element method. A 2-fluid model equipped with chemical reaction equations in argon plasma, heat transfer equation, and Poisson's equation was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A DC voltage source with an amplitude of 1000 V supplied the current of 50 A through a 20 Ohm resistance, which is placed in series with the interrupter. The employed physical model was as described in [14]. The continuity equation of electrons, mass conservation equations of heavy species were considered as well as the heat transfer and Maxwell equations [15][16][17][18][19].…”
Section: Physical Model and Geometry Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…A DC voltage source with an amplitude of 1000 V supplied the current of 50 A through a 20 Ohm resistance, which is placed in series with the interrupter. The employed physical model was as described in [14]. The continuity equation of electrons, mass conservation equations of heavy species were considered as well as the heat transfer and Maxwell equations [15][16][17][18][19].…”
Section: Physical Model and Geometry Simulationmentioning
confidence: 99%
“…In Equations (13) and (14), v electron,th , γ ion , ε ion , ε, Γ electron,injected , and n are the electron thermal velocity, secondary electron emission coefficient, mean energy of the ion secondary emitted electrons, mean energy of thermally emitted electrons, total injected electron flux, and normal vector, respectively. The total injected electron flux was determined by the current flowing through the plasma by the external circuit as described later.…”
Section: Boundary Condition Of the Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…Effects due to change in magnetic field intensity to sustain plasmas have been discussed by several researchers [1][2][3][4][5][6]. Krinberg [1] observed the limit whereby the effect of the applied magnetic field can be used to reduce the size of the plasma column, increase the electron temperature and the average ion charge.…”
Section: Introductionmentioning
confidence: 99%
“…Krinberg [1] observed the limit whereby the effect of the applied magnetic field can be used to reduce the size of the plasma column, increase the electron temperature and the average ion charge. Hashemi et al [2] reported that a constriction of the plasma flow was observed with a decrease in plasma jet radius causing an additional Joule heating in a plasma. Woo et al [5] identified the effect of ion temperature anisotropy associated with the induction of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%